THE ROLE OF SOCIAL POLICY IN THE YOUTH LABOR MARKET IN AZERBAIJAN - GULIYEVA, Khanym Hikmat gizi (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The purpose of the article is to study the impact of social policy on the youth labor market in Azerbaijan, paying special attention to identifying effective strategies and measures that can increase the integration of young people into the labor force. The study aims to analyze the challenges young people face in finding employment, and how various government initiatives, educational reforms and legislative measures can help create a more inclusive and vibrant labor market for young people. During the study, the following methods were chosen as the main research methods: historicity, scientific validity, objective and critical attitude to historical processes, their comparative analysis Novelty: for the first time, an objective attitude towards employment-oriented processes of youth socialization has been identified, the definition of effective strategies for increasing youth employment and their integration into the labor market, contributing to the socio-economic development of Azerbaijan. The study highlights government efforts to improve youth employability through educational reforms, job training, employment incentives and support programs. These initiatives aim to provide young Azerbaijanis with the necessary skills, knowledge and opportunities to succeed in a competitive and globalized job market. The study highlights the various efforts undertaken by the Azerbaijani government through education reforms, vocational training, employment promotion and legislative measures to integrate youth into a dynamic and developing labor market. These initiatives are comprehensive and target both demand and labor market aspects to equip young people with the necessary skills, opportunities and protection. It is noted that the role of social policy in the youth labor market is not only to solve pressing employment problems, but also to invest in the future of the country. Developing a well-integrated, skilled and motivated young workforce is essential to Azerbaijan’s pursuit of economic diversification and sustainable development. This requires a joint effort between government, the private sector, educational institutions and civil society.